ANTIBACTERIAL ACTIVITY OF FENNEL ESSENTIAL OIL AGAINST PROPIONIBACTERIUM ACNES BACTERIA - Wahyu Purwanjani; Jaka Lepangkari; Eka Ammyta PP (Joseph: Journal of Science and Pharmacy, 2021)
Background: Recently, natural ingredients are preferred because of their low level of toxicity to their users. Fennel has good   properties as an antibacterial, so it is necessary to develop another   essential oil taken from fennel to be studied for acne bacteria, namely Propionibacterium acnes. P.acnes is one of the floral bacteria on the surface of the skin, which has a role in the process of forming sebum so that acne occurs. Objective: This research was conducted to obtain the best results from the concentration of essential oils so that the essential oils with the best concentrations could be further developed in cosmetic preparations that are useful as antiacne. Method: Fennel seeds were taken and the steam detailing process was carried out for 7.5 hours. Then after the fennel essential oil was obtained, chemical compounds were tested using the Gas Chromatography-Mass Spectrophotometry (GC-MS) method to determine the chemical content of the fennel essential. Furthermore, testing the antibacterial activity of P.acnes on MHA media by inoculation of bacteria on MHA media and then the discs were immersed in different concentrations of essential oils, namely 2%, 4%, 6% and 8%. After that, compare the results of the essential oil discs with Clydamicyn positive control discs and negative control discs.   Results: The identification of chemical compounds using GCMs shows that the content of several chemical constituents in essential oils is quite high, such as anetol (83.6%), Fenchone (3.58%); Linalool (0.69%); l-Limonene (3.75%); and benzaldehyde (0.41%). The antibacterial activity test of fennel essential oil against P. acnes showed a fairly large inhibitory power of 1.6 cm at a concentration of 6% fennel essential oil. Conclusion: Fennel essential oil has antibacterial activity against P.acnes bacteria so it is possible to develop it into cosmetic preparations that can inhibit the process of acne.